Referees’ Emotions and Performance Perception: The Importance of Stress and Cognitive Appraisal - Canedo Nogueira, Daniela Filipa; Fontes, Liliana; da Silva Gomes, António Rui; Coelho Resende da Silva, Rui Manuel (Cuadernos de Psicología del Deporte, 2022)
The tasks referees must perform are both complex and very important, and are usually associated with high levels of stress. In this study, we aimed to understand the role of stress and cognitive appraisal on referees’ emotions and sports performance perception before the realization of a game. We adopted a critical incident methodology to understand how referees adapt to the stress related to their next game. The study included 708 football referees (646 males), aged between 18 and 53 (M = 26.81; SD = 7.32). We evaluated sources of stress, cognitive appraisal, emotions, and perception of individual performance. Regression analyses pointed out that stress was a main predictor of negative emotions, cognitive appraisal was a predictor of both negative and positive emotions, and that cognitive appraisal also contributed to comprehend the perception of individual performance. In sum, stress and appraisal are important factors to understand the stress experience of referees.